2011
DOI: 10.1002/edn.190
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes specialist nursing in the UK: the judgement call? A review of existing literature

Abstract: Leichter als bisher angenommen kann die elektrochemische NADH‐Regenerierung in sauerstoffhaltigen Medien durchgeführt werden, sodass dieser Regenerationsansatz auch auf NAD(P)H‐abhängige Monooxygenasen angewendet werden kann (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
6
0
3
Order By: Relevance
“…A recent review17 of the clinical effect and cost‐effectiveness of DSNs in the UK emphasised the importance of DSNs to the future of diabetes care. James et al 17. argued that the role of the DSN is becoming fragmented and more research is needed among community DSNs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review17 of the clinical effect and cost‐effectiveness of DSNs in the UK emphasised the importance of DSNs to the future of diabetes care. James et al 17. argued that the role of the DSN is becoming fragmented and more research is needed among community DSNs.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes management team usually consists of general practitioner, diabetologist, diabetes educator, nurse, podiatrist, nutritionist, ophthalmologist and dentist. The patients and their families are also members of the team (2). Numerous clinical trials have shown the effectiveness of nurses in diabetes management (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Per a aquest estudi es va fer una adaptació del qüestionari utilitzat en l'estudi SEND 229 , validat a la llengua castellana, que consta de 39 preguntes repartides en 4 apartats:…”
Section: Instruments De Recollida D'informacióunclassified
“…D'altra banda, s'observa que l'edat mitjana del col·lectiu educador de l'assistència especialitzada es troba en edats properes a la jubilació (51,3 anys), i això pot donar lloc a un problema relacionat amb el recanvi professional. Aquesta dada es corrobora en altres estudis a Europa com, per exemple, a Suècia, on l'edat mitjana de les infermeres especialistes en diabetis és de 53,3 anys 296 , i al Regne Unit, on el 2011, tot i disposar de cursos acreditats d'educadors en diabetis, especulaven que el 44 % es retiraria en un termini de 10 anys, amb poques expectatives de professionals capacitats per poder ocupar els seus llocs de treball 297 . En aquest sentit, a Catalunya, el Máster para la Atención y Educación de las Personas con Diabetes pot ser una oportunitat per cobrir aquests llocs de treball en un termini curt de temps.…”
Section: Discussióunclassified
See 1 more Smart Citation